Менеджмент пружності соціальних бізнес-процесів системи освіти - Бурлуцька, Світлана Владиславівна; Бурлуцький, Сергій Віталійович (My University, 2018)
Метою статті є формування концептуальних засад побудови дієвого менеджменту пружності соціальних бізнес -процесів системи освіти в умовах посткризового відновлення соціально - економічної системи України. В роботі доведено, що соціальна пружність повинна визнаватися в якості одного з основного компонентів в рамках можливості суспільства протистояти серйозним проблемам економічних, природних, техногенних та політичних небезпек. У сфері освіти соціальна пружність та ефективність обумовлюється сукупністю чинників, пов’язаних з спроможністю суб’єктів освітнього процесу досягати позитивних результатів навчання незважаючи на шокові збурення соціально-економічної системи. Запропонована в роботі концепція менеджменту пружності соціальних бізнес -процесів в системі освіти спрямована на забезпечення ефективного відновлення суспільства в умовах шокових збурень та повинна сприяти досягненню більш високих доменів сталості та пружності. Умовою реалізації запропонованої концепції є використання закордонного досвіду – методичних напрацювань Світового Банку та інструментарію програм ERA та SABER. The purpose of the paper is the formulation the conceptual foundations of the effective management of resilience of education social business processes in the post-crisis recovering conditions of the Ukrainian socio -economic system. It has been proved the statement of that social resilience should be recognized as one of the main components in the society's ability to stand up to the serious problems of economic, natural, man -made and political adversity. In the field of education, social resilience and efficiency are determined by a combination of factors associated with the education institutions ability of subjects to achieve positive learning outcomes despite the socio -economic system`s shock fluctuation. The concept of management of the resilience of education social business processes has been aimed at ensuring effective society restoration in the conditions of shock fluctuation and should contribute to the achievement of higher domains of sustainability and resilience has been suggested in the article. The condition for implementing the proposed concept is the use of foreign experience - the methodological developments of the World Bank and the set of tools of the programs ERA and SABER. Summing up the issues addressed in the field of social elasticity, we note that an effective educational system must be sustainable and resilient, depending on a number of parameters, including the availability of a strategic program and risk assessment that are consistent with the goals of social development; social capital, etc. Social capital of society indicates the presence of connecting features of social organization. Together with the economic issues of overcoming crisis phenomena, social elasticity must be recognized as one of the main components in the context of the ability of society to withstand the serious problems of economic, natural, man -made and political dangers.
Keywords: менеджмент; бізнес-процес; соціальна пружність; система освіти; шокові збурення; shock fluctuation; management; business process; social resilience; education system; кафедра економіки праці та менеджменту